Effects of a Syllable-Based Reading Intervention in Poor-Reading Fourth Graders - Müller, Bettina; Richter, Tobias; Karageorgos, Panagiotis; Krawietz, Sabine; Ennemoser, Marco (Frontiers in Psychology, 2017)
In transparent orthographies, persistent reading fluency difficulties are a major cause of poor reading skills in primary school. The purpose of the present study was to investigate effects of a syllable-based reading intervention on word reading fluency and reading comprehension among German-speaking poor readers in Grade 4. The 16-session intervention was based on analyzing the syllabic structure of words to strengthen the mental representations of syllables and words that consist of these syllables. The training materials were designed using the 500 most frequent syllables typically read by fourth graders. The 75 poor readers were randomly allocated to the treatment or the control group. Results indicate a significant and strong effect on the fluency of recognizing single words, whereas text-level reading comprehension was not significantly improved by the training. The specific treatment effect provides evidence that a short syllable-based approach works even in older poor readers at the end of primary school.